2022
DOI: 10.29271/jcpsp.2022.02.177
|View full text |Cite
|
Sign up to set email alerts
|

ChromagarTM Col-Apse for Detection of Colistin Resistance in Clinical Isolates of Multidrug Resistant Gram Negative Bacilli

Abstract: Objective: To determine the diagnostic accuracy of CHROMagar TM COL-APSE, for detection of colistin resistance in clinical isolates of multi drug resistant (MDR) gram negative bacilli (GNB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…In this study, CHROMAgar Col- APSE produced the highest rate of MEs and a high VME second only to that of the in-house Rapid NP test (Tables 1-2), particularly for Klebsiella spp. Although the specificity recorded in this study and that of Osei Sekyere et al (at 66,67%) agree, two other studies recorded a significantly higher specificity of ≥ 97% [11,22,23]. These discrepancies could be attributed to the different bacterial inoculum concentrations used.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In this study, CHROMAgar Col- APSE produced the highest rate of MEs and a high VME second only to that of the in-house Rapid NP test (Tables 1-2), particularly for Klebsiella spp. Although the specificity recorded in this study and that of Osei Sekyere et al (at 66,67%) agree, two other studies recorded a significantly higher specificity of ≥ 97% [11,22,23]. These discrepancies could be attributed to the different bacterial inoculum concentrations used.…”
Section: Discussioncontrasting
confidence: 52%
“…These discrepancies could be attributed to the different bacterial inoculum concentrations used. Ali et al demonstrated that when a 0.5 McFarland standard inoculum was used, colistin- susceptible isolates were able to grow on the media [23], whereas the same isolates were inhibited when the inoculum was diluted to a density of 1×105 CFU/mL. Therefore, the high rate of MEs in this present study could be due to the inoculum used being a 0.5 McFarland standard (1.5×108 CFU).…”
Section: Discussionmentioning
confidence: 78%